Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3748/wjg.v22.i15.4034
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib after resection improves the outcome of BCLC stage C hepatocellular carcinoma

Abstract: Sorafenib after SR was well-tolerated. Patients who received sorafenib after SR had better outcomes compared to patients who received only SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Cancer staging and postoperative treatment varied in patients with or without PVI. Currently, clinical trials have been conducted to validate various techniques for example surgical resection, transcatheter arterial chemoembolization (TACE), hepatic arterial infusion chemotherapy, radioembolization and sorafenib for the treatment of HCC [2729]. Besides, attention has been paid to understand the promoting factors of PVI and corresponding mechanisms [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer staging and postoperative treatment varied in patients with or without PVI. Currently, clinical trials have been conducted to validate various techniques for example surgical resection, transcatheter arterial chemoembolization (TACE), hepatic arterial infusion chemotherapy, radioembolization and sorafenib for the treatment of HCC [2729]. Besides, attention has been paid to understand the promoting factors of PVI and corresponding mechanisms [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that perioperative treatment with hepatectomy could improve the prognosis of HCC patients with PVTT. Previous studies have reported the outcomes of combination treatment based on surgical resection for HCC patients with PVTT (Table ) . The MST and 1‐year OS rate after combination treatment ranged from 11.5 to 37 months and from 46.8% to 100%, respectively.…”
Section: Surgical Resection Combined With Multidisciplinary Treatmentmentioning
confidence: 99%
“…Previous studies have reported the outcomes of combination treatment based on surgical resection for HCC patients with PVTT (Table 2). 24,[33][34][35][36][37][38][39][40] The MST and 1-year OS rate after combination treatment ranged from 11.5 to 37 months and from 46.8% to 100%, respectively. In a randomized controlled trial, Peng et al reported that estimated 1-, 3-and 5-year survival rates were better in the TACE after surgical resection group (50.9%, 33.8%, and 21.5%) than in the surgical resection alone group (33.3%, 17.0%, and 8.5%).…”
Section: Surgical Resection Combined With Multidisciplinary Treatmentmentioning
confidence: 99%
“…Prevention of postoperative recurrence is the focus of postoperative management in HCC with TT in the IVC and RA. Measures to prevent postoperative recurrence include postoperative oral sorafenib administration (30)(31)(32) and adjuvant TACE (33,34).…”
Section: Treatmentmentioning
confidence: 99%